Enchanting Math AudibleBook: Insights from Teachers, University Students, and Young Learners - Alim, Jesi Alexander; Oktaviani, Cici; Hermita, Neni; Putra, Zetra Hainul (Department of Mathematics Education, Faculty of Mathematics and Natural Sciences, UNY, 2023)
Reading is an essential activity of learning. In this study, the researchers investigated the opinions of elementary school teachers, university students majoring in elementary school teacher education, and elementary school students on the mathematics audible book